Seveneves - Stephenson, Neal (New York : William Morrow, an imprint of HarperCollinsPublishers, 2015)
A catastrophic event renders the earth a ticking time bomb. In a feverish race against the inevitable, nations around the globe band together to devise an ambitious plan to ensure the survival of humanity far beyond our atmosphere, in outer space.
Keywords: Disasters -- Fiction; Survival -- Fiction; Earth (Planet) -- Fiction; Outer space -- Exploration -- Fiction; Psychological fiction; Science fiction